Difference between revisions of "009B Sample Midterm 3, Problem 5"
Jump to navigation
Jump to search
(Created page with "<span class="exam">Evaluate the indefinite and definite integrals. ::<span class="exam">a) <math>\int \tan^3x ~dx</math> ::<span class="exam">b) <math>\int_0^\pi \sin^2x~dx<...") |
|||
Line 1: | Line 1: | ||
<span class="exam">Evaluate the indefinite and definite integrals. | <span class="exam">Evaluate the indefinite and definite integrals. | ||
− | + | <span class="exam">(a) <math>\int \tan^3x ~dx</math> | |
− | + | ||
+ | <span class="exam">(b) <math>\int_0^\pi \sin^2x~dx</math> | ||
Line 8: | Line 9: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |Recall the trig | + | |'''1.''' Recall the trig identity |
+ | |- | ||
+ | | <math style="vertical-align: -3px">\tan^2x+1=\sec^2x</math> | ||
|- | |- | ||
− | |''' | + | |'''2.''' Recall the trig identity |
|- | |- | ||
− | | | + | | <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}</math> |
|- | |- | ||
− | |How would you integrate <math style="vertical-align: -1px">\tan x~dx?</math> | + | |'''3.''' How would you integrate <math style="vertical-align: -1px">\tan x~dx?</math> |
|- | |- | ||
| | | | ||
− | + | You could use <math style="vertical-align: 0px">u</math>-substitution. | |
+ | |- | ||
+ | | First, write <math style="vertical-align: -14px">\int \tan x~dx=\int \frac{\sin x}{\cos x}~dx.</math> | ||
|- | |- | ||
| | | | ||
− | + | Now, let <math style="vertical-align: -5px">u=\cos(x).</math> Then, <math style="vertical-align: -5px">du=-\sin(x)dx.</math> | |
+ | |- | ||
+ | | Thus, | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \tan x~dx} & = & \displaystyle{\int \frac{-1}{u}~du}\\ | \displaystyle{\int \tan x~dx} & = & \displaystyle{\int \frac{-1}{u}~du}\\ | ||
&&\\ | &&\\ | ||
Line 31: | Line 38: | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 41: | Line 49: | ||
|- | |- | ||
| | | | ||
− | + | <math style="vertical-align: -14px">\int \tan^3x~dx=\int \tan^2x\tan x ~dx.</math> | |
|- | |- | ||
− | |Since <math style="vertical-align: -5px">\tan^2x=\sec^2x-1,</math> we have | + | |Since <math style="vertical-align: -5px">\tan^2x=\sec^2x-1,</math> we have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int (\sec^2x-1)\tan x ~dx}\\ | \displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int (\sec^2x-1)\tan x ~dx}\\ | ||
&&\\ | &&\\ | ||
Line 56: | Line 64: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we need to use <math>u</math>-substitution for the first integral. | + | |Now, we need to use <math>u</math>-substitution for the first integral. |
|- | |- | ||
| | | | ||
− | + | Let <math style="vertical-align: -5px">u=\tan(x).</math> | |
+ | |- | ||
+ | |Then, <math style="vertical-align: -1px">du=\sec^2x~dx.</math> | ||
+ | |- | ||
+ | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int u~du-\int \tan x~dx}\\ | \displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int u~du-\int \tan x~dx}\\ | ||
&&\\ | &&\\ | ||
Line 74: | Line 86: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |For the remaining integral, we also need to use <math>u</math>-substitution. | + | |For the remaining integral, we also need to use <math>u</math>-substitution. |
|- | |- | ||
|First, we write | |First, we write | ||
|- | |- | ||
| | | | ||
− | + | <math style="vertical-align: -14px">\int \tan^3x~dx=\frac{\tan^2x}{2}-\int \frac{\sin x}{\cos x}~dx.</math> | |
+ | |- | ||
+ | |Now, we let <math style="vertical-align: 0px">u=\cos x.</math> | ||
+ | |- | ||
+ | |Then, <math style="vertical-align: -1px">du=-\sin x~dx.</math> | ||
|- | |- | ||
− | | | + | |Therefore, we get |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\frac{\tan^2x}{2}+\int \frac{1}{u}~dx}\\ | \displaystyle{\int \tan^3x~dx} & = & \displaystyle{\frac{\tan^2x}{2}+\int \frac{1}{u}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 97: | Line 113: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |One of the double angle formulas is <math style="vertical-align: -5px">\cos(2x)=1-2\sin^2(x).</math> | + | |One of the double angle formulas is |
+ | |- | ||
+ | | <math style="vertical-align: -5px">\cos(2x)=1-2\sin^2(x).</math> | ||
|- | |- | ||
− | |Solving for <math style="vertical-align: -5px">\sin^2(x),</math> we get <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}.</math> | + | |Solving for <math style="vertical-align: -5px">\sin^2(x),</math> we get |
+ | |- | ||
+ | | <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}.</math> | ||
|- | |- | ||
|Plugging this identity into our integral, we get | |Plugging this identity into our integral, we get | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\int_0^\pi \frac{1-\cos(2x)}{2}~dx}\\ | \displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\int_0^\pi \frac{1-\cos(2x)}{2}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 117: | Line 137: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\left.\frac{x}{2}\right|_{0}^\pi-\int_0^\pi \frac{\cos(2x)}{2}~dx}\\ | \displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\left.\frac{x}{2}\right|_{0}^\pi-\int_0^\pi \frac{\cos(2x)}{2}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 127: | Line 147: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. | + | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. |
|- | |- | ||
− | |Let <math style="vertical-align: -1px">u=2x | + | |Let <math style="vertical-align: -1px">u=2x.</math> |
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: -1px">du=2~dx</math> and <math style="vertical-align: -18px">\frac{du}{2}=dx.</math> |
|- | |- | ||
− | |We have <math style="vertical-align: -5px">u_1=2(0)=0</math> and <math style="vertical-align: -5px">u_2=2(\pi)=2\pi.</math> | + | |Also, since this is a definite integral and we are using <math style="vertical-align: 0px">u</math>-substitution, |
+ | |- | ||
+ | |we need to change the bounds of integration. | ||
+ | |- | ||
+ | |We have <math style="vertical-align: -5px">u_1=2(0)=0</math> and <math style="vertical-align: -5px">u_2=2(\pi)=2\pi.</math> | ||
|- | |- | ||
|So, the integral becomes | |So, the integral becomes | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\frac{\pi}{2}-\int_0^{2\pi} \frac{\cos(u)}{4}~du}\\ | \displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\frac{\pi}{2}-\int_0^{2\pi} \frac{\cos(u)}{4}~du}\\ | ||
&&\\ | &&\\ | ||
Line 148: | Line 172: | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math>\frac{\tan^2x}{2}+\ln |\cos x|+C</math> | + | | '''(a)''' <math>\frac{\tan^2x}{2}+\ln |\cos x|+C</math> |
|- | |- | ||
− | | '''(b)''' <math>\frac{\pi}{2}</math> | + | | '''(b)''' <math>\frac{\pi}{2}</math> |
|} | |} | ||
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']] |
Revision as of 11:21, 9 April 2017
Evaluate the indefinite and definite integrals.
(a)
(b)
Foundations: |
---|
1. Recall the trig identity |
2. Recall the trig identity |
3. How would you integrate |
You could use -substitution. |
First, write |
Now, let Then, |
Thus, |
|
Solution:
(a)
Step 1: |
---|
We start by writing |
|
Since we have |
|
Step 2: |
---|
Now, we need to use -substitution for the first integral. |
Let |
Then, |
So, we have |
|
Step 3: |
---|
For the remaining integral, we also need to use -substitution. |
First, we write |
|
Now, we let |
Then, |
Therefore, we get |
|
(b)
Step 1: |
---|
One of the double angle formulas is |
Solving for we get |
Plugging this identity into our integral, we get |
|
Step 2: |
---|
If we integrate the first integral, we get |
|
Step 3: |
---|
For the remaining integral, we need to use -substitution. |
Let |
Then, and |
Also, since this is a definite integral and we are using -substitution, |
we need to change the bounds of integration. |
We have and |
So, the integral becomes |
|
Final Answer: |
---|
(a) |
(b) |